Entropy Generation for Peristaltic Blood Flow with Casson Model and Consideration of Magnetohydrodynamics Effects - BHATTI, Muhammad Mubashir; ABBAS, Munawwar Ali; RASHIDI, Mohammad Mehdi (Walailak Journal of Science and Technology (WJST), 2016)
In this article, entropy generation on peristaltic blood flow of the Casson fluid model is investigated under the influence of magnetohydrodynamics. The present mathematical analysis consists of continuity equations, momentum, and energy equations, which are simplified using the approximation of long wavelength and creeping flow regime. The reduced coupled differential equations are solved analytically, and a closed form of solution is presented. The impact of all the physical parameters of interest, such as the Brinkmann number, Hartmann number, and Casson fluid parameter, are taken into account. Trapping phenomena is also discussed with the help of contours. It is observed that the Casson fluid parameter and magnetic parameter show similar effects on velocity. Further, it is also observed that entropy profile behaves as an increasing function for all the pertinent parameters.